Morfología del mercado laboral en Colombia (1998)
ABSTRACT: This articule describes the trends in the labour market during the last decade. The rising behaviour of the labour force offering shows an emphasis on the participation of working women. From the perspective of demand on labour force phenomenon of "terciarización" of the working market outline. The offer of service is the activity of highest dynamism in the generation of workin position, which contrast the sorrow behaviour of sectors like agriculture, construction and industry. The unbalances of working market are shown in unemployement rising informality, underemployment and temporal jobs. The most vulnerable groups to unemployment still are women and young people. The cyclic unemployment reaches levels no registered before in the recent history of the country. However, more than a quantitative problem, the labor unbalance is a matter of working quality and low wages, that hits negatively in the life quality of colombian people. Therefore, the are a direct association with the high levels of poverty and the obvious concentretion of income. Finally this articule mentions the employment policies and labour that have been discussed in the country for the last year. This proposals are different because os their origin, time and conception, since the come from actors with not always matching interests, and they are even contradictory.